2013
DOI: 10.15376/biores.8.2.2967-2980
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Py-GC/FID and Wet Chemistry Analysis for Lignin Determination in Wood and Pulps from Eucalyptus globulus

Abstract: The kraft pulps produced from heartwood and sapwood of Eucalyptus globulus at 130 ºC, 150 ºC, and 170 ºC were characterized by wet chemistry (total lignin as sum of Klason and soluble lignin fractions) and pyrolysis (total lignin denoted as py-lignin). The total lignin content obtained with both methods was similar. In the course of delignification, the py-lignin values were higher (by 2 to 5%) compared to Klason values, which is in line with the importance of soluble lignin for total lignin determination. Pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…The authors concluded that vanillin, isoeugenol, dihydroconiferyl alcohol, and G-C ¼ C ¼C structures that separate spruce and larch from pine. E. globulus total lignin content was measured using pyGC-FID [240]. This study measured a strong linear correlation (R 2 ¼0.979) between wet chemistry total lignin and pyGC-FID, regardless of the pulping conditions.…”
Section: Pyrolysismentioning
confidence: 80%
See 3 more Smart Citations
“…The authors concluded that vanillin, isoeugenol, dihydroconiferyl alcohol, and G-C ¼ C ¼C structures that separate spruce and larch from pine. E. globulus total lignin content was measured using pyGC-FID [240]. This study measured a strong linear correlation (R 2 ¼0.979) between wet chemistry total lignin and pyGC-FID, regardless of the pulping conditions.…”
Section: Pyrolysismentioning
confidence: 80%
“…Thermochemical techniques have occasionally been utilized for the measurement of total lignin content [66,[238][239][240]. Alves and co-authors utilized analytical pyrolysis and GC-FID to measure the lignin content of a variety of hard-and softwoods [66,238,239].…”
Section: Pyrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…The distinctive bands of S and G lignin, as well as cellulose, can be eliminated as correlative to these vibrational modes. Although its content in hardwoods is often minute, Acacia and Eucalyptus species have been determined to contain potentially 2-9 % H lignin, depending on the age of the trees [18][19][20][21]. Further chemical or instrumental analysis, such as thioacidolysis or 2D nuclear magnetic resonance, is required to determine if these vibrational modes correspond to H lignin.…”
Section: -1657mentioning
confidence: 99%